Living precariously: property guardianship and the flexible city - Vasudevan, Alexander; Dawson, Gloria; Ferreri, Maria (Wiley, 2016)
In this paper we examine the precarious everyday geographies of property guardianship in the United Kingdom. Temporary property guardianship is a relatively new form of insecure urban dwelling existing in the grey area between informal occupation, the security industry and housing. Young individuals, usually in precarious employment, apply to intermediary companies to become temporary 'guardians' in metropolitan centres, most notably in London. The scheme allows guardians to pay below market rent to live in unusual locations while ‘performing’ live-in security arrangements that are not considered as a form of ‘work’. The experiences of becoming and living as a property guardian can be ambivalent and contradictory: guardians express economic and social advantages to being temporary, while also exposing underlying anxieties with ‘flexible living’. In this paper we offer a detailed description of the various practices of property guardianship and how they must be understood on the one hand, in light of recent geographical scholarship on housing insecurity and, on the other hand, as an example of a precarious subjectivity that has become normalised in recent decades in cities of the global North. Drawing on indepth interviews with long-term property guardians in London, we unpack the narratives and rationales of university educated and highly skilled individuals for whom the city is a site of intensified insecurity and flexible negotiations. In the end, we conclude that the form of permanent temporariness experienced by property guardians needs to be understood as a symptom of wider dynamics of work and life precarisation in urban centers and argue that it is imperative to extend recent geographical debates around work and life insecurity to include new housing practices and their role in co-constituting urban precarity.